Peran Perempuan dan Kolaborasi Lintas Generasi untuk Keluarga Berdaya Indonesia Maju - Triyani, Yustina; Meiden, Carmel; Pane, Zulfikar Ikhsan; Pangaribuan, Leonard; Suhartono, Sugi; Mutiarawati, Elisabeth Vita (Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Community Service Activities (PkM) were carried out by the IBIKKG PkM Team in the context of the Jakarta Hindu Dharma Women's Independence Celebration (WHDI) on August 5, 2024, which was held in the form of seminars and ongoing mentoring. This continuous PkM activity aims to increase the awareness and understanding of WHDI members regarding the importance of the role of marriage in the family and community. Through presentations and discussions, participants gained insight into how women can be the main drivers in the family, both as educators, caregivers and economic drivers. This activity also emphasizes the importance of cross-generational collaboration to preserve cultural values and improve family welfare. As a result, the seminar succeeded in building networks and collaborations between various women's groups, creating synergy in efforts to empower women and strengthen families in Indonesia.